Does Foreign Portfolio Investment Reach Small Listed Firms? - Knill, April M. (World Bank, Washington, DC, 2012)
Using a unique dataset, the author examines the impact of foreign portfolio investment on the capital issuance behavior of small listed firms. The author finds that foreign portfolio investment is associated with an increased probability of small firm security issuance in all nations, regardless of property rights development. Evidence suggests the mechanism by which this occurs is a freeing up of capital in domestic markets when large firms utilize the foreign investment directly. Debt levels in nations where property rights are more developed increase, suggesting that foreign portfolio investment may reach small firms through the banking channel as well as capital markets in these nations.